Spontaneous coronary artery dissection as a marker of undifferentiated connective tissue dysplasia: a case report - Ya. B. Khovaeva; A. L. Korovin; Ya. A. Sychugov; L. V. Ermachkova; N. P. Moiseenko (Кардиоваскулярная терапия и профилактика)
The article presents a case report of spontaneous coronary artery dissection (SCAD) in the young woman with signs of undifferentiated connective tissue dysplasia (UCTD). The patient was admitted urgently with a clinical and electrocardiographic signs of acute ST-segment elevation coronary syndrome. The patient underwent a coronary angiography, which revealed a type D linear intimal dissection. The decision was made to perform balloon vasodilation with the placement of a drug-eluting stent. With multicomponent therapy, the patient’s condition improved. Physical examination revealed external markers of UCTD. Therefore, it was quantified by systems and organs. The patient had no other cardiovascular diseases, previous infection, or other trigger factors. She was discharged with recommendations to continue the prescribed therapy. This case report demonstrates SCAD as a rare cause of acute myocardial infarction in a young patient. The background for SCAD development in this case was UCTD. Algorithms for managing patients with SCAD against the background of UCTD have not been defined and require further study.